Porous bioactive glass microspheres prepared by flame synthesis process - Kraxner, Jozef; Michalek, Martin; Romero, Acacio Rincon; Elsayed, Hamada; Bernardo, Enrico; Boccaccini, Aldo R.; Galusek, Dušan (Materials Letters, 2019)
A scaleable, low cost processing method to prepare porous bioactive glass (BG) microspheres is presented. Glass powder with composition based on 45S5 BG and exhibiting irregularly shaped particles was fabricated by conventional melting. Glass powder was alkali activated to induce pore formation during the following flame synthesis step. Porous microspheres, with diameters ranging between 45 and 75 µm, were successfully prepared and characterized by X-ray diffraction, Fourier-transform infrared spectroscopy, and scanning electron microscopy with energy-dispersive X-ray spectroscopy. The porous bioactive glass microspheres are promising candidates for applications in bone regeneration, tissue engineering, and as carriers for controlled drug delivery.
CRIS-Team Scopus Importer:2019-09-24
Keywords: Alkaline activation; Bioactive glass; Flame synthesis; Porous microspheres